Ethnobotany of food plants used by Minangkabau Community in Lima Puluh Kota District, West Sumatra, Indonesia - ASIH RAHAYU AJENG AGESTI; NUNIK SRI ARIYANTI; TATIK CHIKMAWATI; YOHANES PURWANTO (Biodiversitas Journal of Biological Diversity, 2023)
Abstract. Agesti ARA, Ariyanti NS, Chikmawati T, Purwanto Y. 2023. Ethnobotany of food plants used by Minangkabau Community in Lima Puluh Kota District, West Sumatra, Indonesia. Biodiversitas 24: 2756-2767. The Minangkabau tribe is well known for its culture and cuisine, but documents on their knowledge and wisdom in the utilization of food plants are still limited. This study aims to inventory plant species used for food by Minangkabau community, assess their importance and economic value, and analyze the important landscapes where the food plants are obtained. This study was conducted in six villages representing different level of modernization in Lima Puluh Kota District, West Sumatra which is one of the centers of origin of Minangkabau ancestral. Data were collected through open, semi-structured and structured interviews with key informants and respondents. The Pebble Distribution Method (PDM) is used for scoring activities. Data were analyzed to show the use values (UVs), local user's value index (LUVI), index of cultural significance (ICS), and economic value of the food plants. The interviewed informants mentioned 154 plant species from 51 families were used for food. Cocos nucifera L. has the most various uses as food (highest UVs) and is the most important cultivated plant for the Minangkabau culture (ICS) in all the six villages. The most important food plant species based on a community perspective (highest LUVI) is Oryza sativa L. The wild plants having the highest LUVI and ICS differed among the villages. Plants with high economic value include O. sativa, Durio zibethinus Murray and Citrus aurantium L. The landscapes considered important are paddy fields and fields because they provide staple food. Information from this study can support food diversification to achieve food security based on the local knowledge on the diversity of food plant species and potential landraces in Minangkabau community.